2000
DOI: 10.1038/35016590
|View full text |Cite
|
Sign up to set email alerts
|

The temporal response of the brain after eating revealed by functional MRI

Abstract: After eating, the human brain senses a biochemical change and then signals satiation, but precisely when this occurs is unknown. Even for well-established physiological systems like glucose-insulin regulation, the timing of interaction between hormonal processes and neural events is inferred mostly from blood sampling. Recently, neuroimaging studies have provided in vivo information about the neuroanatomical correlates of the regulation of energy intake. Temporal orchestration of such systems, however, is cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
194
3
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(216 citation statements)
references
References 24 publications
18
194
3
1
Order By: Relevance
“…Different experimental approaches have been used to examine similar questions; some designs have involved feeding a liquid meal (a proportion of the individual's total energy requirements) to participants while in the scanner, 24 or giving participants a fixed-energy glucose drink. 9,11 The aim of this study was to measure changes in neural activity and the conscious experience of the participants with PWS after consumption of a normal meal, increasing the ecological validity of the design. It is acknowledged that using fixed-energy meals does not take individual energy requirements into account; however, for the higher-energy meal at least, some participants consumed a significant proportion of their total daily energy requirement -yet a pattern of neural activation representative of satiety was still not found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different experimental approaches have been used to examine similar questions; some designs have involved feeding a liquid meal (a proportion of the individual's total energy requirements) to participants while in the scanner, 24 or giving participants a fixed-energy glucose drink. 9,11 The aim of this study was to measure changes in neural activity and the conscious experience of the participants with PWS after consumption of a normal meal, increasing the ecological validity of the design. It is acknowledged that using fixed-energy meals does not take individual energy requirements into account; however, for the higher-energy meal at least, some participants consumed a significant proportion of their total daily energy requirement -yet a pattern of neural activation representative of satiety was still not found.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence to suggest a hypothalamic basis, 7,8 which was recently supported by a functional neuroimaging study in three individuals with PWS. 9 Shapira et al 9 showed a significant delay in the negative response of the hypothalamus to glucose ingestion in those with PWS, in comparison to obese 10 and normal-weight 11 groups. However, an imaging study in a control group of nonobese individuals, 12 together with research from other groups, [13][14][15] has shown that the motivation to eat is controlled by an extensive system of reciprocally connected neural areas, beyond the hypothalamus, mediating both the intrinsically derived hunger drive to eat and the extrinsically derived incentive to eat.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…After preprocessing, the 2dTCA analysis is performed using programs written in IDL software (ITT Visual Information Solutions, Boulder, CO) based on the modifications of the original TCA methods [Gao and Yee, 2003;Liu et al, 2000;Lu et al, 2006;Morgan et al, 2004;Yee and Gao, 2002;Zhao et al, 2004]. Each voxel time course is treated individually as an array, Z(1:N).…”
Section: Tca Vs 2dtca Methodsmentioning
confidence: 99%
“…Other types of data-driven techniques such as hierarchical clustering Keogh et al, 2005;Stanberry et al, 2003], fuzzy clustering [Baumgartner et al, 2000], and temporal clustering analysis (TCA) [Gao and Yee, 2003;Liu et al, 2000;Lu et al, 2006;Makiranta et al, 2005;Yee and Gao, 2002;Zhao et al, 2004] use clustering of similar fMRI signal time courses to group and determine voxel time courses of interest, instead of partitioning into components. Previous studies have reported that these clustering algorithms outperform PCA [Baumgartner et al, 2000] and ICA techniques for fMRI analysis [Meyer-Baese et al, 2004].…”
Section: Introductionmentioning
confidence: 99%